Becoming Jihadis: radicalization and commitment in Southeast Asia - Chernov-Hwang, Julie (Causes and consequences of terrorism, 2023)
Why does someone join an extremist group? What are the pathways via which individuals join such groups? How does one show commitment to an extremist group? Why does someone participate in acts of terrorism? Drawing on 175 interviews with current and former members of Islamist extremist groups in Indonesia and the Philippines, Becoming Jihadis: Radicalization and Commitment in Southeast Asia answers these questions by exploring the socio-emotionalunderpinnings of joining an extremist group. This book argues that social ties play a critical role at every juncture in the joining process, from initial engagement to commitment to participation in jihad experiences, paramilitary training, and terrorism. It unpacks the process by which members build a sense ofcommunity, connection, solidarity, and brotherhood; how they come to trust and love one another; and how ideology functions as a binding agent, not a cause. Becoming Jihadis draws its conclusions from broad patterns data based on nearly a decade of iterated interviews with current and former members of Islamist extremist groups between 2010 and 2019, as well as partial life histories detailing the journeys of men and women who joined Indonesian and Filipino extremist groups. This book makes a unique contribution to the literature on terrorism and radicalization for students, practitioners, and policymakers.